Etnická a socio-profesná identita a konflikt (na príklade multietnického priestoru zaoceánskych lodí) - Zuzana Krátká (AntropoWebzin, 2010)
In my doctoral thesis I analyse way of life of crew members sharing the multiethnic territory of cruise ships. I tended to investigate this theme after I had experienced an extraordinary cooperation of people from all around the world on cruise ships. My goal is to sum up basic conditions which should be fulfilled in any multiethnic society to ensure that there would not be any conflicts between its habitants. According to my hypothesis there is a need of other than ethnical identity which could unify them on other than ethnical basis. In the territory of cruise ships it is socio-professional identity of  „crew member“. From all factors in which we can observe socio-professional identity of crew members I attend communication and value system.